HIDROLISIS KITIN MELALUI FERMENTASI SEMI PADAT UNTUK PRODUKSI N-ASETILGLUKOSAMINA - Iwan Saskiawan; Rini Handayani (BERITA BIOLOGI, 2011)
N-acetyl-D-glucosamine (GlcNAc), the monomeric unit of polymer chitin has attracted much attention for their therapeutic activity in osteoarthritis.It is mainly produced by acid hydrolysis of chitin which affect the environmental problem because of its acidic wastes.Therefore, it is need to develop the new method for GlcNAc production. The aim of this experiment is to produce GlcNAc by mean of submerged fermentation of chitin. The preliminary study showed that fermentation of chitin by Aspergillus sp.501 produced higher GlcNAc than that of Saccharomyces sp. It was 1.39 ng/ml and 1.07 ng/ml. Then the Aspergillus sp. 501 was used in optimation of GlcNAc production. The effect of pH and nitrogen course such as bacto peptone, yeast extract, amonium sulfat and urea to GlcNAc production was examined. Then the product of GlcNAc was precipited by vacum evapotated and freeze dryed. The results showed that the highest of production GlcNAc of 2.228 ng/mL was obtained on pH 4 of medium solid state fermentation using urea as Nitrogen source at 10 days incubation.